Peran Pemerintah Dalam Mitigasi Dampak Corona Virus Disease (Covid-19) Terkait Hubungan Industrial - Rahmaturyadi, Ismail (Universitas Negeri Surabaya, 2023)
The World Health Organization (WHO) has declared Corona Virus Disease (Covid-19) a pandemic, and Covid-19 has spread very quickly throughout the world, including Indonesia. The government has taken several ways to prevent the spread of this virus, namely by implementing the Large-Scale Social Restrictions (PSBB) policy. This study aims to analyze the government's role in mitigating the impact of Covid-19 related to industrial relations. This study uses a normative juridical research method, namely the law approach. The results of this study are the urgency of the government's role in mitigating the impact of Covid-19 related to industrial relations. Apart from that, the role of the government with its various policies is also important because in dealing with the Covid-19 pandemic, the economic conditions of the people are completely disorganized so that the legal policies implemented by the government can restore the economy of the people who have been significantly affected due to the Covid-19 pandemic. The form of the government's role in maintaining industrial relations between employers and government workers has provided a stimulus for employers and workers/laborers affected by Covid-19 in the form of credit restructuring, incentives for workers affected by layoffs and policies in the field of taxation.